EXPERIENCE SHOCKS OF STRATEGIC FOOD CONSUMERS IN INDONESIA DURING COVID-19 PANDEMIC - Fitrotul Laili; Wiwit Widyawati; Dian Islami Prasetyaningrum (Agricultural Socio-Economics Journal, 2022)
COVID-19's negative externalities disrupted the supply of several commodities. Meanwhile, to combat the spread of COVID-19, various countries have implemented a lockdown policy, which impacts the economy's balance. Consumers' risks are increasing due to economic changes caused by the COVID-19 pandemic, which affects the higher level of volatility of various agricultural commodities in Indonesia, particularly strategic commodities. Thus, this research was designed to examine the experience shock of strategic food consumers during Covid-19 pandemic. The ARCH/GARCH model was used to describe the strategic food price movement pattern using a set of weekly consumer price data from March 2020 until August 2021. This study found price volatility of strategic food commodities is classified into three categories. For starters, the extreme volatility of commodities such as garlic and cayenne pepper indicates that future buyers will face more significant uncertainty and risk. Furthermore, these commodities will generate fluctuating price swings in the future, resulting in greater experience shock for consumers. Second, commodities with high price volatility, such as rice, chicken meat, eggs, shallots, and sugar, signal that these commodities will subject consumers to a huge shock due to their high price volatility. Third, minimal volatility, such as that found in meat, red chilli, and cooking oil, indicates that customers will face less uncertainty in the future.